Recent Trends of Antibiotic Resistance in Staphylococcus aureus Causing Clinical Mastitis in Dairy Herds in Abruzzo and Molise Regions, Italy - Franca Rossi; Ilaria Del Matto; Maria Antonietta Saletti; Luciano Ricchiuti; Patrizia Tucci; Lucio Marino (MDPI AG, 2023)
This study aimed to investigate the recent trends of antibiotic resistance (AR) prevalence in Staphylococcus aureus isolated from the milk of animals with clinical mastitis in areas of the Abruzzo and Molise regions in Central Italy. Fifty-four S. aureus isolates were obtained from routine testing for clinical mastitis agents carried out in the author institution in the years 2021 and 2022 and were analyzed for phenotypic resistance to eight antibiotics recommended for testing by European norms and belonging to the antibiotic classes used for mastitis treatment in milk-producing animals. Moreover, the presence of 14 transferable genetic determinants encoding resistance to the same antibiotics was analyzed using qPCR tests developed in this study. Phenotypic resistance to non-β-lactams was infrequent, with only one 2022 isolate resistant to clindamycin. However, resistance to the β-lactam cefoxitin at concentrations just above the threshold of 4 µg/mL was observed in 59.2% of isolates in both years, making these isolates classifiable as methicillin-resistant. The AR genotypes detected were the blaZ gene (50% of 2021 isolates and 44.4% of 2022 isolates), aphA3-blaZ- ermC/T (one 2021 isolate), aphA3-ant6-blaZ-ermC/T (one 2021 isolate), blaZ-ermB (one 2022 isolate) and mecA-mph (one 2022 isolate). An inquiry into the veterinarians who provided the samples, regarding the antimicrobials prescribed for mastitis treatment and criteria of usage, indicated a possible causal relation with the AR test results. The occurrence of AR genotypes did not increase in time, most probably reflecting how mastitis was treated and prevented in farms. However, the frequently observed cefoxitin resistance needs to be explained genotypically, further monitored and limited by modifying antibiotic usage practices. The identification of a mecA-positive isolate in 2022 suggests further investigation if this genotype is emerging locally.